A rainfall forecasting method using machine learning models and its application to the Fukuoka city case - Sumi, Monira S.; Zaman, Faisal M.; Hirose, Hideo (Zielona Góra: Uniwersytet Zielonogórski)
In the present article, an attempt is made to derive optimal data-driven machine learning methods for forecasting an average daily and monthly rainfall of the Fukuoka city in Japan. This comparative study is conducted concentrating on three aspects: modelling inputs, modelling methods and pre-processing techniques.
Keywords: rainfall forecasting; machine learning; multi-model method; pre-processing; model ranking